Republic of Moldova : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2008)
The first section of this paper is an attempt to examine the interest rate channel of monetary policy transmission in Moldova and to estimate the strength and the speed of the interest rate pass-through. The next section provides a background on Moldovan financial markets, liquidity conditions, and the current framework of monetary policy. The following section sets out the formal model used to estimate the strength and the speed of the pass-through, and the last session discusses results.